The effect of psychological empowerment, organizational justice, affective commitment, and self-efficacy on task performance: Research on probation officers in Indonesia - Wulandari, Sri; Syahlani, Dudi Hendrakusuma; Pusparini, Elok Savitri (Annals of Human Resource Management Research, 2025)
Purpose: This research aims to analyze the effects of psychological empowerment, organizational justice, affective commitment, and self-efficacy on task performance among probation officers in Indonesia. Additionally, this research examines the mediating roles of affective commitment and self-efficacy in the relationship between psychological empowerment and organizational justice, focusing on task performance. Methodology/approach: The approach used in this research is quantitative, employing a survey method. Data were collected through the distribution of online questionnaires that successfully captured 360 respondents, and after the data cleaning process, 328 valid data points were analyzed using Structural Equation Modeling (SEM) through the Lisrel application. Results/findings: The results showed that psychological empowerment, organizational justice, affective commitment, and self-efficacy have a significant and positive impact on task performance. Additionally, it was found that affective commitment and self-efficacy also serve as significant mediators in strengthening the influence of psychological empowerment and organizational justice on task performance. Conclusion: The conclusion of this research reveals that both individual psychological factors and perceptions of organizational justice play a crucial role in enhancing employee task performance. Limitations: The limitations of this research lie in its use of a cross-sectional design and the limited scope of one type of functional position, specifically probation officers. Contribution: This research makes a practical contribution to the Directorate General of Corrections and Correctional Centers by developing performance improvement strategies based on a human resource management approach that incorporates both individual and organizational factors.